Development and application of MOQUICO code to study molten corium-concrete interaction. (1st September 2020) - Xu, Zhichun; Zhang, Yapei; Lin, Bo; Luo, Simin; Zhou, Yukun; Su, G.H.; Tian, Wenxi; Qiu, Suizheng
Highlights: A molten corium-concrete interaction (MCCI) analysis code MOQUICO is developed. The code is validated using various experiments. The MCCI analysis for light water reactor plants is performed using the developed code. Abstract: After the Fukushima nuclear accident, great attention is being paid to the late-phase behavior of the severe accident in the reactor, especially the molten corium-concrete interaction (MCCI). The MCCI process is very complex, involving physical and chemical reactions, heat and mass transfer processes. Many factors will affect the final result, with a high degree of uncertainty and there are still many unknowns based on current knowledge. In this paper, aimed at the MCCI phenomena in the containment cavity during a hypothetical accident in the nuclear power plant, an MCCI analysis code MOQUICO was developed by coupling the models of molten corium-concrete heat transfer, the concrete pyrolysis, and the corium cooling characteristics. The code MOQUICO was validated using the CCI-2, CCI-3 and SURC-2 tests with limestone-common sand concrete (LCS), siliceous concrete (SIL), and basaltic concrete (BAS), respectively. The simulant axial and radial ablation depths, upward heat flux and melt temperature agreed well with the experimental measurements. Afterwards, the code was used to simulate the typical PWR and BWR nuclear power plants. The ablation depth and gas production were analyzed for both simulations. Furthermore, the corium cooling was studied with eight different water injection moments for PWR and sensitivity analysis for decay heat and concrete type was conducted for BWR. The analysis proved that the developed code is capable of simulating MCCI and related phenomena of Light Water Reactor (LWR).